Edukasi Obesitas pada Remaja di Pondok Pesantren Al Hidayah Kota Jambi - Rahmawati, Helfi; Fatmawati, Tina Yuli; Jeki, Andicha Gustra (Prosiding Seminar Kesehatan Nasional, 2024)
Indonesia is experiencing a rapid change in diet and physical activity patterns known as the ‘nutrition transition’, where high-calorie processed foods are becoming a visible part of the population’s daily consumption, while sedentary lifestyles are becoming more common, leading to a greater prevalence of overweight and even obesity. The results of the Riskesdas show that there is an increase in the prevalence of obesity in those aged 18 years and over, from 14.8% to 21.8%. In the obese population, the prevalence is higher in women (29.3%) than in men (14.5%). The prevalence is higher in urban areas (25.1%) than in rural areas (17.8%). Meanwhile, according to age group, obesity is highest in the 40-49 year age group (29.6%). In Jambi province, the prevalence of obesity is 17.5%. A survey conducted by a team with one Pondok Caretaker said that there has been no education about obesity. Teenagers are accustomed to consuming high-calorie foods, buying fast food and rarely exercising. The purpose of this community service is to increase the knowledge of students about the Importance of Preventing Obesity. The community service methods applied are lectures, discussions, guidance, including understanding, causes, and prevention of obesity. Community service activities were carried out in October 2023 to January 2024 on 20 students, located at PP Al Hidayah, Jambi City. The results of this community service activity showed an increase in students' knowledge after being given health education about obesity by 96%.